Study on the effectiveness of public private partnership (PPP) project in Malaysia - Zuraini, Zaimuddin (2014)
Public Private Partnership (PPP) is a globally accepted public sector procurement mechanism whereby the government engages commitment from private sector and transfers a certain level of responsibilities to the private sector in providing public facilities or services. PPP involves the transfer to the private sector the responsibility to finance and manage a package of capital investment and services including the construction, management, maintenance, refurbishment and replacement of public sector assets such as buildings, infrastructure, equipment and other facilities, which creates a standalone business. Several cases of BOT ventures that had run into problems due to cost overruns, unrealistic price and income projections, and legal disputes between private operators and the government. PPP projects also would incur higher cost of capital than the traditional public financing due to incorporation of equity risk as risk are borne by private sector. This study was carried out based on literature review and a questionnaire survey. Average index calculation was employed to assess level of effectiveness of Public Private Partnership (PPP) project in Malaysia. This study were identified to highlight the effectiveness, of Public Private Partnership project in Malaysia, to investigate the best conditions under which PPP is more appropriate and to identify the benefits, success and difficulties of PPP. The overall result shows the suitable type of project for the PPP project is value for money and the reason for implementation the PPP is for large projects. The factor leading to successful project of PPP is value for money achieved and the profound problems of the PPP is the government interference.